装具着用下での遊脚様式が裸足歩行における左立脚相の安定性低下に影響を及ぼした脳出血後左片麻痺の症例 - 楠, 貴光; 大沼, 俊博; 鈴木, 俊明; 歳森, 大輝 (関西理学療法, 2021)
The present case had right putamen hemorrhage 5 years ago and presented with left hemiplegia. The patient had used a left lower limb orthosis for 5 years. The long-duration usage of the orthosis reduced the chance of muscle activity in the left lower limb, promoted hypotonia in the left triceps surae and left quadriceps muscles, and additionally promoted hypotonia in the left lower limb. These were assumed to be causative factors of the swing habit. Additionally, the habitual swing pattern of the left lower extremity resulted in secondary dysfunctions such as hypotonia of the anterior and posterior gluteus medius muscles and hypertonia of the left iliocostalis and quadratus lumborum. It was assumed that it also affected the decrease in stability of barefoot walking. Therefore, to improve the stability of barefoot walking, it was important to improve not only the dysfunction of the left lower limb but also the habitual swing mode of the left lower limb.